Perception among Healthcare Professionals of the Use of Social Media in Translating Research Evidence into Clinical Practice in Mangalore - Bhaskaran Unnikrishnan; Priya Rathi; Daivik Shah; Abhay Tyagi; Anish V. Rao; Koyel Paul; Joe Tomy (International Journal of Telemedicine and Applications)
Introduction. Social media has a potential to bring about major changes in the healthcare system. Objective. To find out the pattern of use of social media among healthcare professionals (HCPs) and perception, facilitators, and barriers of using social media, to translate evidence into clinical practice. Method. We conducted a cross-sectional study among 196 HCPs of institutions attached to a university using a self-administered questionnaire. Result. 97.3% used social media; however, only 63.4% used it for research. YouTube was the most preferred media. Majority of people believed that social media enables wide range of evidence over the shorter span of time, poses a threat to privacy, and cannot replace face to face interaction. Perceived barriers were the privacy concern, unprofessional behavior, lack of reliability, and information overload. Conclusion. There is a need for the development of appropriate guidelines for sharing the research output among various stakeholders using social media.